Jornalismo gonzo na revista Trip: uma análise de gênero - Krette Júnior, Wilson (2006)
This thesis attempts to study the Gonzo Journalism in Brazil. The purpose is to analyse the reportage published by Trip magazine, which is an example of this journalistic genre, as well as to explore linguistic and speech procedures. Firstly, the work tries to review shortly, based on specialised bibliography, the linguistics development until the Speech Analysis School. The aim is to offer a brief but necessary base of theory to the reader. The essay presents the concepts and a historic trajectory of the three following speech genre of journalism: Literary Journalism, New Journalism and Gonzo Journalism. The corpus will be analised from the perspectives of genre and textual elements that are typical of Gonzo Journalism. It means to observe thematic and structural components. Hence, the chosen theories are the speech analysis of French School and the genre study proposed by the Russian critic Mikhail Bakhtin (1895-1975). The study's main concern is to study the genre concept in order to categorize the journalistic corpus. The research is focused on Gonzo Journalism, since it analyses two selected news reporting published in 2005 and 2006. However, it was necessary to present the other journalistic genres with the aim of verify their fluid character, contributions and influences. Besides, the work deals with the types of support and the development of the adopted magazine, regarding the international context. Created in 1986, Trip is recognized, in Brazil, due to the space dedicated to Gonzo reportage. It is considered alternative, contemporary and it became an editorial phenomenon between young and influent people. The magazine has today 187 thousand readers. Despite the vast critic works produced in the last years about speech analysis, this thesis supports that this reportage style is undervalued by the academia. Therefore, the major bulk is to contribute to Gonzo Journalism studies, as soon as to reveal its importance, originality and specificity.